Efecto in vitro del extracto etanólico de tropaeolum majus mastuerzo sobre staphylococcus aureus meticilino resistente ATCC 25923 - Aspauza Lescano, Tahireh (2015)
The aim of this experimental study was to determine the in vitro effect of ethanolic extract of leaves and flowers Tropaeolum majus "Nasturtium" on Staphylococcus aureus methicillin resistant (MRSA) ATCC 25923. Susceptibility testing was performed using the disk diffusion method. MRSA strains were spreaded on Mueller Hinton agar; discs with different concentrations of the extract were set on the agar. The plates were incubated at 37 ° C; halos were measured after 18 hours; all disks had inhibition zone whose size increased in direct proportion to the relative concentrations used. Macrodilution method was also used with concentrations of 10.535, 52.675, 105.35, 158.025 and 210.7 ug / ml of the extract, to which was added MRSA inoculum. These were incubated at 37 ° C for 18 hours, then set on Mueller Hinton agar plates to determine colony forming units (CFU), which were counted 18 hours later. Growth inhibitory effect was observed MRSA. The minimum inhibitory concentration found was 210.7 ug / ml. It is concluded that the ethanolic extract of leaves and flowers Tropaeolum majus has inhibitory activity in vitro on the growth of MRSA strains ATCC 25923